Hubbard U calculations for gap states in dilute magnetic semiconductors - Fukushima, T.; Katayama-Yoshida, H.; Sato, K.; Bihlmayer, G.; P. Mavropoulos; Bauer, D. S. G.; R. Zeller; P.H. Dederichs (JOURNAL OF PHYSICS-CONDENSED MATTER, 2014)
On the basis of constrained density functional theory, we present ab initio calculations for the Hubbard U parameter of transition metal impurities in dilute magnetic semiconductors, choosing Mn in GaN as an example. The calculations are performed by two methods: (i) the Korringa-Kohn-Rostoker (KKR) Green function method for a single Mn impurity in GaN and (ii) the full-potential linearized augmented plane-wave (FLAPW) method for a large supercell of GaN with a single Mn impurity in each cell. By changing the occupancy of the majority t(2) gap state of Mn, we determine the U parameter either from the total energy differences E(N + 1) and E(N - 1) of the (N +/- 1) -electron excited states with respect to the ground state energy E(N), or by using the single-particle energies for n(0) +/- 1/2 occupancies around the charge-neutral occupancy n(0) (Janak's transition state model). The two methods give nearly identical results. Moreover the values calculated by the supercell method agree quite well with the Green function values. We point out an important difference between the `global' U parameter calculated using Janak's theorem and the `local' U of the Hubbard model.